ENHANCING LANGUAGE PROFICIENCY THROUGH PROJECT-BASED LEARNING: CULTIVATING COMMUNICATION SKILLS WITH CONTEXTUAL TASKS - Shahina Shukhratova (Ustozlar uchun, 2025)
Abstract: Project-Based Learning (PBL) has emerged as a transformative pedagogical approach in language education, emphasizing the importance of contextual tasks in fostering effective communication skills. This article explores the methodological aspects of PBL in language acquisition, highlighting how meaningful projects can enhance learner engagement, motivation, and linguistic proficiency. Through a comprehensive literature review, this study identifies key strategies for implementing PBL in language classrooms and discusses the implications for educators. The findings suggest that contextual tasks not only facilitate language learning but also prepare students for real-world communication challenges.